PENGARUH LIKUIDITAS, KOMITE AUDIT, KUALITAS AUDIT DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG - Muhammad Nazhif Faqih Zulfikar, (2023)
This research is a quantitative study that aims to examine the effect of liquidity, audit committee, audit quality and firm size on audit report lag. In this study, audit report lag is measured based on the length of days it takes to receive an independent auditor's report on fiscal financial statements, in terms of the company's book closing date as of December 31 to the date recorded in the independent auditor's report. The sample in this study totaled 201 companies listed on the Indonesia Stock Exchange from 2019 to 2021, the sample in this study used purposive sampling. Testing the hypothesis in this study using Multiple Regression Analysis with the Stata 14 program, with a significance level of 5%. The results of this study are (1) liquidity has no effect on audit report lag. (2) audit committee has no effect on audit report lag (3) audit quality has negative effect on audit report lag (4) company size has positive effect on audit report lag. Keyword : Liquidity, Audit Committee, Audit Quality, Company Size